Unlocking the Challenging Pathways of Youth Participation in Ghana’s Youth Employment and Entrepreneurial Development Agency - Edward Brenya; Dominic Degraft Arthur; Janet Nyarko (Journal of Social and Development Sciences, 2021)
Youth participation in public policies such as the employment policy process has gained prominence in academic and policy literature. Despite this, research on youth participation in the employment policy process has received little attention in Ghana. This paper draws on documentary analysis to unlock the challenging pathways of youth participation in Ghana’s youth employment and entrepreneurial development agency. The paper finds that a web of challenges such as insufficient access to information, over-politicization of GYEEDA, poor level of coordination of stakeholders, and prevalence of diversity and social exclusion are embedded in obstructing the youth participation in GYEEDA. The study recommends that policymakers such as the government and other stakeholders should provide adequate measures to ensure that beneficiaries such as the youths are engaged in the design, formulation, and execution of the youth employment policy process in Ghana.